Multi-scale phase-field modeling of layer-by-layer powder compact densification during solid-state direct metal laser sintering. (May 2021) - Wang, Xiao; Liu, Yuan; Li, Like; Yenusah, Caleb.O.; Xiao, Yaohong; Chen, Lei
Abstract: Solid-state direct metal laser sintering (S-DMLS) builds structures by using laser energy to sinter powder particles in a layer-by-layer manner. Powder size distribution (PSD) is an important parameter governing the densification of powders and the overall quality of as-built S-DMLS parts. Therefore, this work aims to reveal the underlying mechanism of layer-by-layer powder compact densification during the S-DMLS with different PSDs via a multi-scale computational framework: 1) a powder-based 3D heat transfer simulation is conducted to predict the thermal response at the macroscale during laser heating; 2) the obtained thermal information is input to a non-isothermal phase-field model to simulate the sintering behavior of powder particles in a layer-by-layer manner at the mesoscale. Using stainless steel 316 L as an example, a narrow PSD presents a small volume of gap between powders with an elevated effective thermal conductivity, causing a deep laser-induced heating zone that promotes full grain coalescence and reduces porosity during the S-DMLS. Furthermore, a bimodal powder mixture with an optimized size ratio can also effectively reduce the porosity of as-built S-DMLS parts. Moreover, the effect of layer-wise manufacturing on the densification is comprehensively explored. Finally, the influences of laser beam size and scanning speed are discussed. Graphical abstract: Unlabelled Image Highlights: A multi-scale framework has been developed to simulate the layer-by-layer densification behavior of powders during S-DMLS. Heat transfer, partial melting and grain coalescence have been considered in the developed nonisothermal phase-field model. Relatively thin layer thickness was favorable for reducing the porosity in fabricated S-DMLS parts. Narrow PSD presents a larger laser-heated zone and and reduced porosity during S-DMLS.